Central mucoepidermoid carcinoma of maxilla with radiographic appearance of mixed radiopaque–radiolucent lesion: a case report - Sherin, S (The British Institute of Radiology., 2011)
Mucoepidermoid carcinoma is the most common primary malignancy of the salivary glands. Central mucoepidermoid carcinomas are extremely rare in the jaws. Here we report a case of a 19-year-old central mucoepidermoid carcinoma in a young female patient which was asymptomatic throughout her history and which radiographically simulated a fibro-osseous lesion; both features misled the clinical diagnosis. A radiographic picture of mixed radiopaque–radiolucent appearance in central mucoepidermoid carcinoma is extremely rare. The long duration is also uncommon for a malignant lesion. This case report adds a new dimension to the clinical and radiographic picture a central mucoepidermoid carcinoma can reveal.